Beginning of the metal age in the central Balkans according to the results of the archeometallurgy - Jovanović B. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The gradual development of the primary copper metallurgy in Balkans starts with production of small jewelry pieces and ends with the serial production of massive tools and weapons. It is confirmed that this metallurgy depended on the contemporary mining, i.e. the available sources of the raw materials. It is also corroborated by the discovery of two Early Eneolithic copper mines: Rudna Glava in Eastern Serbia and Ai-Bunar in Bulgaria /first half and the middle of the 5th millennium BC/. These mines are also the evidence for the local exploitation of the carbonate copper minerals - malachite and azurite. The technology employed is close to the former flint mining in the Late Neolithic; massive pebbles obtained from the neighboring alluvial deposits were used as mining hammers. Identical technology was employed in the mines dating from the later periods /Rudnik, Central Serbia, Jarmovac, Priboj na Limu/. The Vinča culture of the central Balkan followed all metallurgical phases of introduction of metal and use of the carbonate ores /Gradac I - III phase/. This long process of including the metal in wider use lasted generally from the middle of the 5th millennium BC to the end of the 4th millennium BC, i.e. to the appearance of the Bronze Age.